THE CONCEPT, CONTENT AND STAGES OF FORMATION OF ACTIVE CITIZENSHIP COMPETENCE IN STUDENTS - Buvorayeva Gulruh Shoikrom qizi (Bright Mind Publishing, 2025)
The article discusses the concept, content and stages of formation of active civic competence in students and the expansion of democratic processes in modern society, reforms aimed at fully ensuring the rights and freedoms of the individual, determine civic education as one of the main tasks of education. From this point of view, the formation of citizenship sets before the education system the task of not only imparting knowledge, but also educating a person who will be formed as an active citizen. This process includes the formation of legal awareness, social responsibility, a sense of involvement in the affairs of the state and society, a culture of critical thinking and communication in the student.
Keywords: Competition, system, education, competence, potential, task, homeland, global, expert.